Digital Magazines in Lithuania - Velykytė, Gabija (Knygotyra, 2024)
The article analyzes the transition of magazines published in Lithuania in 2021 to the digital space. The aim is to reveal the aspects of magazine digitization in Lithuania and investigate the percentage of magazines which already have digital versions, which magazines have become digital, and what determines the digitization of magazines. It has been established that only a third of magazines have digital versions in today’s Lithuania. The digitization of magazines is driven by the desire of publishers to give readers access to the magazine through a broader range of channels along with the ability to reach a more significant flow of readers. An important aspect that promotes the digitization of magazines is the demand from various sponsoring organizations to increase access forms. Publishers choose magazine hosting platforms and formats to keep the magazine hosting process straightforward and cost-efficient. It has been investigated that the taxation of the magazine’s digital version in Lithuania is an infrequent phenomenon. An issuehas been determined that publishers rarely formalize digital versions by assigning them separate ISSNs. The reason is the ignorance of the requirement that the printed and digital versions of the same journal must have separate ISSNs. Currently, the digitization of magazines is still evolving: publishers are in no hurry to get acquainted with the requirements for publishing digital magazines, digital versions of magazines are generally basic, and there is a lack of high-quality, interactive, attractive arrangements of digital magazines.
Keywords: digitalization; magazine; periodical